UPAYA BADAN PERLINDUNGAN PEKERJA MIGRAN INDONESIA (BP2MI) PROVINSI RIAU DALAM MENINGKATKAN KEAMANAN PEKERJA MIGRAN INDONESIA (PMI) TUJUAN MALAYSIA TAHUN 2019-2022 - Rahmat Pranata Putra; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research will discuss the efforts of the Indonesian Migrant Worker Protection Agency, abbreviated as BP2MI, in improving the safety of Indonesian Migrant Workers (PMI) with Malaysia in the 2019 to 2022 period. This research concentrates on the task force unit under the auspices of BP2MI, namely the Riau Indonesian Migrant Worker Protection Service Center (BP3MI). This research is theoretically constructed using a neorealism perspective and is supported by role theory according to KJ Holsti. The formulation of all arguments, data, facts, and theoretical framework in this study uses a qualitative description method. This study also uses groups as a level of analysis. The results of this study are that BP3MI Riau as the Task Implementing Unit of BP2MI has made various efforts to improve PMI security with Malaysia both before, during and after PMI has worked. BP3MI has coordinated with all parties in resolving problems experienced by PMI. The efforts made by BP2MI through BP3MI Riau can be seen to what extent it has implemented Law no. 18 of 2017, and its efforts in dealing with problems based on existing case studies. Keywords: Efforts, PMI, BP2MI, Security, Cases